2019
DOI: 10.12659/msm.917851
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Suppresses IL-1β-Induced Apoptosis in Chondrocytes via Phosphatidylinositol 3-Kinases (PI3K)/Akt Signaling Inhibition

Abstract: Background Salidroside, a natural dietary isothiocyanate, has been widely studied for its multiple effects, including promoting proliferation, anti-inflammation, and anti-apoptosis. In the present study, these effects of Salidroside were explored to assess whether it could prevent osteoarthritis (OA) in vitro . Material/Methods The cytotoxic and proliferating effects of Salidroside on chondrocytes were detected by use of the Cell Counting Kit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Rats were divided into five groups (n=10): Control group (Healthy rats were given saline treatment); ACLT, ACLT model; ACLT + Sal (12.5 mg/kg), OA rats were treated with 12.5 mg/kg Sal; ACLT + Sal (25 mg/kg), OA rats were treated with chondrocytes. 40 Similarly, this study found that Sal promoted the proliferation of chondrocytes in OA rats and inhibited the expression of apoptotic proteins (cleaved caspase 3 and cleaved caspase 9). The main factors for the progression of OA are chronic inflammation and progressive structural changes in joint tissues.…”
Section: Discussionmentioning
confidence: 53%
“…Rats were divided into five groups (n=10): Control group (Healthy rats were given saline treatment); ACLT, ACLT model; ACLT + Sal (12.5 mg/kg), OA rats were treated with 12.5 mg/kg Sal; ACLT + Sal (25 mg/kg), OA rats were treated with chondrocytes. 40 Similarly, this study found that Sal promoted the proliferation of chondrocytes in OA rats and inhibited the expression of apoptotic proteins (cleaved caspase 3 and cleaved caspase 9). The main factors for the progression of OA are chronic inflammation and progressive structural changes in joint tissues.…”
Section: Discussionmentioning
confidence: 53%
“…Salidroside is a natural antioxidant originally extracted from medicinal food plant Rhodiola rosea 137 and possesses potential anti-inflammatory 138 , anti-viral 139 , and anti-cancer 140 properties. Salidroside was previously shown to exhibit tumor-suppressive activity by modulating multiple pathways including, Notch1 141 , STAT3 138 , and PI3K/AKT 142 . However, these direct tumor cytotoxic effects mediated by salidroside required relatively high dose both in vitro and in vivo 140 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variety of natural products have emerged as milder options for the treatment of OA in recent years [44,45]. Recent studies showed that salidroside (Sal) could protects against apoptosis and inflammatory response in chondrocytes via inhibition of NF-κB activation and Phosphatidylinositol 3-Kinases (PI3K)/Akt Signaling [46], [47], [48]. However, the effect of Sal on osteoarthritis in vivo and the underlying mechanisms remains unclear.…”
Section: Discussionmentioning
confidence: 99%